Sanksi Pemberhentian dengan Tidak Hormat Prajurit TNI atas Pertimbangan Hakim Militer karena Ketidaklayakan Berdinas Lagi di Lingkungan Militer - Arief Fahmi Lubis (Jurnal Media Administrasi, 2021)
Provisions regarding dishonorable discharge are regulated in Article 53 paragraph (1) of Government Regulation Number 39 of 2010 concerning Administration of TNI Soldiers, which regulates dishonorable discharge from military service, as an implementation of the provisions of Article 62 paragraph (3) of Law Number 34 of 2004 concerning Indonesian national army. The aim of this research is to show that the norm for imposing an additional penalty of dismissal by a judge in a court trial is Article 26 paragraph (1) of the Criminal Code which confirms that the defendant, based on the crime he committed, is deemed no longer fit to remain in the military. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that from the perspective of Military Criminal Procedure law, it can be said that dismissal is the sole authority of the Military Judge taking into account the unfitness of the soldier to be retained to continue serving in the military environment, so that this authority cannot be delegated to a civilian Judge, because the decision will be made basis by the TNI leadership to be followed up. For these military members, dismissal from military service is the end of their career and service within the Indonesian National Army (TNI), the consequences of which will be followed by the termination of the rights they have received so far.